Nigerians with diabetes and their mental health in the context of diabetes care and management: A scoping review - Victor-Aigbodion, Vera (Universitas Negeri Padang, 2023)
This review aimed to ascertain the prevalence of mental health issues among people with diabetes in Nigeria, the nature of care available for them and the effectiveness of available interventions or management strategies used to treat diabetes-related mental health challenges. Four databases, Google Scholar, PubMed, PsycINFO and Cochrane, were searched. Thirteen studies that focused on the prevalence of mental health challenges among diabetes patients were selected for data extraction and analyses. Another set of five studies was also selected to analyze the effectiveness of diabetes care available to diabetes patients with mental health challenges. This scoping review shows that the prevalence rate of mental health problems among Nigerian diabetic patients is high. It also shows inadequate care or intervention provided to the patients. However, the few available care and interventions were found to be very effective.